Membranous glomerulonephritis: a retrospective study on prognostic outcome - Maifata, Sadiq Mu'azu; Hod, Rafidah; Zakaria, Fadhlina; Abd Ghani, Fauzah (Association of Specialist Medical Doctors in Academics (ASMeDA), Sokoto, Nigeria, 2021)
Background: Membranous glomerulonephritis (MGN) is one of the most common causes of nephrotic syndrome in non-diabetic adults, accounting for up to one-third of biopsy diagnostics in some regions. A watchful waiting strategy has been adopted to accurately assess the success of MGN. In this study, we predict prognostic risk factors for primary MGN patients for effective intervention. Materials and Methods: This is a retrospective study design involving 125 biopsy-proven MGN subjects on follow-up from January 2012 to October 2019 in Hospital Serdang and Hospital Kuala Lumpur, Malaysia. Result and Conclusion: After the median follow-up of 36 (15.0-57.0) in months, 26 (20.8%) consisting of 17 (13.6%) primary MGN and 9 (7.2%) secondary MGN subjects achieved complete remission while 17 (13.6%) and 10 (8.0%) of primary and secondary MGN subjects respectively achieved spontaneous remission. Subjects with nephrotic range proteinuria have 2.917 odds more at risk of primary MGN while subjects with hypertension have 2.417 odds risk of primary MGN compared to those with no hypertension at presentation. Multiple logistic regression models retained only factors directly associated with MGN with only nephrotic range proteinuria associated with primary MGN. Those with nephrotic range proteinuria were 3.04 times the odds of primary MGN when compared with those without nephrotic syndrome (95% C. I = 1.089, 8.472). The nephrotic syndrome could be used to determine the prognosis in patients with primary MGN especially those at risk of end-stage renal disease.